Italian Southern Issue and the Territorial Development Policies: Analysis of Social Plausibility of Narratives by Multiple Voices - Vinci, Fiorella (E|C, 2020)
Through which social mechanisms could the southern question have contributed to regenerating the backwardness of the southern regions? Placed in the tradition of sociology of public action, the article focuses on the relationship between scientific knowledge and public action. It analyzes the influence of meridional literature practiced in the early 90s of the twentieth century on the European territorial development policies. The different capacities of the Italian regions in implementing European cohesion policy are understandable by reconstructing the social plausibility of narratives proposed by different subjects (social scientists, journalists, regional government officials) who re-elaborate the constituent themes of the southern question for specific audiences.